Singapore Case Note: What happens when a party to an MSA has a change of heart? - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2018)
Hot off the press, the case of Chan Gek Yong v Violet Netto (practising as L F Violet Netto) and another and another matter [2018] SGHC 208 (‘Violet Netto’) decided by the Singapore High Court provides us with clues as to the Court’s general attitude towards mediation and mediated settlement agreements (‘MSAs’). It is useful to reflect on the Singapore Court’s attitude towards mediation in light of the introduction of the Singapore Mediation Act (No. 1 of 2017) – which has been in effect since 1 November 2017 – and the emergence of the draft Singapore Convention on Mediation, which is expected to be adopted by the UN General Assembly later this year with a signing ceremony expected in August 2019.